Effect of high-volume fly ash, curing temperature and water to cement ratio on strength development and durability of concrete - Hlabangana, Mthulisi (My University, 2020)
High volume fly ash concrete presents a sustainable and environmentally friendly alternative to production of construction materials. However, it has not been fully embraced in high strength concrete applications due to the challenge of reduced early age compressive strength. This study investigated the influence of high volume fly ash replacement, curing temperature, water to cement ratio and Ca(OH)2 activation on compressive strength and durability of concrete. High strength concrete incorporating ordinary Portland cement and ultra-fine fly ash contents of 25%, 35% and 50% was used to prepare samples for compressive strength and durability testing. Ultra-fine fly ash was used in order to attain high strength concrete. A total of 16 concrete mixes were prepared. Eight concrete mixes had a w/c ratio of 0.45 and the other eight mixes had aw/c ratio of 0.35. Ca(OH)2 was added to eight concrete mixes in order to activate the fly ash and improve early age compressive strength and durability. Concrete cubes of 100mm dimensions were cast and cured in water at either 23⁰C or 40⁰C. The concrete properties measured included compressive strength, chloride conductivity, oxygen permeability and water absorption. Compressive strength tests were done at 1 day, 3 days, 7 days, 28 days, 90 days and 180 days. The results showed that some fly ash concrete mixes yielded higher compressive strength compared to the ordinary portland cement concrete mixes. Adding Ca(OH)2 and curing at 40⁰C significantly improved the rate of compressive strength development of fly ash concrete. Durability index tests were conducted at the age of 28 days in accordance with the South African durability index testing methods. Concrete with water to cement ratio of 0.35 yielded higher compressive strength and durability results compared to concrete with water to cement ratio of 0.45. Curing at 40⁰C reduced the late age strength of ordinary Portland cement concrete whereas curing at 40⁰C and adding Ca(OH)2 improved the strength of fly ash concrete. 50% fly ash concrete was the most responsive to Ca(OH)2 activation and high temperature curing. The chloride conductivity index for ordinary Portland cement concrete was significantly higher than that of fly ash concrete. Fly ash concrete cured at 40⁰C was more resistant to chloride penetration compared to fly ash concrete cured at 23⁰C. All the durability index test results signified concrete of high quality. An economic analysis for the binder material indicates that high volume fly ash replacement yielded significant economic benefits
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020